Genetic evidence for the role of non-human primates as reservoir hosts for human schistosomiasis. - Tadesse Kebede; Nicolas Bech; Jean-François Allienne; Rey Olivier; Berhanu Erko; Jerome Boissier (Public Library of Science (PLoS), 2020)
Background Schistosomiasis is a chronic parasitic disease, that affects over 207 million people and causes over 200,000 deaths annually, mainly in sub-Saharan Africa. Although many health measures have been carried out to limit parasite transmission, significant numbers of non-human primates such as Chlorocebus aethiops (Ch. aethiops) (vervet) and Papio anubis (baboon) are infected with S. mansoni, notably in Ethiopia, where they are expected to have potentially significant implications for transmission and control efforts. Objective The objective of this study was to assess and compare the genetic diversity and population structure of S. mansoni isolates from human and non-human primates free-ranging in close proximity to villages in selected endemic areas of Ethiopia. Methods A cross-sectional study was conducted in three transmission sites: Bochesa, Kime and Fincha. A total of 2,356 S. mansoni miracidia were directly isolated from fecal specimens of 104 hosts (i.e. 60 human hosts and 44 non-human primates). We performed DNA extraction and PCR amplification using fourteen microsatellite loci. Results At population scale we showed strong genetic structure between the three sample sites. At the definitive host scale, we observed that host factors can shape the genetic composition of parasite infra-populations. First, in male patients, we observed a positive link between parasite genetic diversity and the age of the patients. Second, we observed a difference in genetic diversity which was high in human males, medium in human females and low in non-human primates (NHPs). Finally, whatever the transmission site no genetic structure was observed between human and non-human primates, however, there appears to be little barriers, if any, host specificity of the S. mansoni populations with cross-host infections. Conclusion Occurrence of infection of a single host with multiple S. mansoni strains and inter- and intra-host genetic variations was observed. Substantial genetic diversity and gene flow across the S. mansoni population occurred at each site and non-human primates likely play a role in local transmission and maintenance of infection. Therefore, public health and wildlife professionals should work together to improve disease control and elimination strategies.